The Reconciliatory Basis between the Integrity of Administrative Decisions and the Suspension of its Implementation - Saeed, Dana Abdul- Kareem (Journal of Legal and Political Studies, 2021)
his paper focuses on the reconciliatory basis between an essential principle in jurisprudence and comparative administrative judiciary, which is the principle of integrity of administrative decision and the non-stance effect of appealing administrative decisions on the one hand, and judicial suspension of the implementation of administrative decision on the other hand; due to its importance in practice, which results in creating preventive judicial monitoring, when the main purpose of resorting to the court is to avoid effects that cannot be remedied before the administration executes its action or even before its contested behavior produces all its effects and temporarily suspends these effects until a judgment is issued in the case by the authority. On the other hand, they represent a conflict between the public interest and the interest of the individuals for whom the decision has caused damages, which imposes on court a hazardous task embodied in reconciling the interest of the individual (the plaintiff) as well as the interest of the administration itself in order to avoid, in the case of a final ruling of abolishing its decision, responsibility for implementing this decision, and the claim for compensation for the damages arising as the result of abolishing the decision, particularly since the suspension of implementation is one of the dangerous authority that the court takes on freedom of administration, as it involves issuing an order contrary to the principle of separation of powers, specifically separating the administrative authority from the judicial authority, by refraining from implementing the decision issued that considers to be in favor of public interest.
Keywords: reconciliatory basis; jurisprudence; judicial suspension; judicial monitoring; hazardous task